The impact of a short course of three lipid lowering drugs on fat oxidation during exercise in healthy volunteers. Issue 809 (March 1993) - Head, A.; Jakeman, P. M.; Kendall, M. J.; Cramb, R.; Maxwell, S.
Abstract : We examined the impact of three lipid lowering drugs on fat oxidation during a 120 minute treadmill walk, at an exercise intensity of 50% maximal oxygen uptake (VO2 max). Subjects (N = 24) were healthy male volunteers with normal serum chemistry, assigned to three groups (n = 8). Group A received simvastatin 20 mg twice daily, Group B received gemfibrozil 600 mg twice daily, Group C received acipimox 600 mg twice daily. Each subject performed two 120 minute walks, once with drug, and once with placebo (4 days treatment plus a final dose on the morning of the exercise trial). Treatment order was reversed for half of each group. Compared to placebo, simvastatin treatment, had no impact on fat oxidation (40.9 +/- 8.6% vs 40.9 +/- 9.7%), or on plasma concentration of free fatty acids (FFA), glycerol or glucose. Treatment with gemfibrozil, showed lower fat oxidation (32.3 +/- 13.9% vs 39.7 +/- 7.9%), and lower plasma concentrations of FFA and glycerol, but differences did not reach significance at the 0.05 level. Acipimox treatment, produced significantly lower fat oxidation (36.9 +/- 12.8% vs 50.2 +/- 16.1%, P = 0.011), and lower plasma concentrations of FFA and glycerol (P = < 0.0001 and P = < 0.0001, respectively). Plasma glucose showed a trend toward lower values with acipimox (P = 0.088). These data demonstrate that selective lipid lowering drugs can reduce fat availability for exercise metabolism, placing increased demands on carbohydrates which may reduce exercise tolerance.